2011
DOI: 10.1007/s11082-011-9493-4
|View full text |Cite
|
Sign up to set email alerts
|

Solid-core square-lattice photonic crystal fibers: comparative studies of the single-mode regime and numerical aperture for circular and square air-holes

Abstract: In this paper we have studied solid-core square-lattice PCFs with circular and square shaped air-holes. We have estimated the V-parameter by using the step-index fiber approximation (SIFA) and calculated numerical apertures for the structures considered. In order to estimate the effective core radius of the structure with the square shaped air-holes we have used an approximation based on the air-filling fraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…In [43], the authors have presented a comparative study of the single mode behaviour and the numerical aperture of a solid core PCF with circular and square air holes arranged in square lattice. They showed that the two structures become multimode when increasing the air filling fraction in the cladding region.…”
Section: Page 5 Of 36mentioning
confidence: 99%
“…In [43], the authors have presented a comparative study of the single mode behaviour and the numerical aperture of a solid core PCF with circular and square air holes arranged in square lattice. They showed that the two structures become multimode when increasing the air filling fraction in the cladding region.…”
Section: Page 5 Of 36mentioning
confidence: 99%
“…1 and we have compared their characteristics with those of circular ones [25], where is the diameter of the circular air-holes, Λ is the pitch of the air hole array, that is, the distance between hole centers, and (= ) and are the diameters of an elliptical air-hole in the -and -direction, respectively. Now, we define the ellipticity as = / .…”
Section: Optical and Geometrical Parameters Of The Fibermentioning
confidence: 99%
“…It is a convenient measure of the ability of an optical fiber to capture light from a wide-angle source and generally a higher NA indicates a higher source-to-fiber coupling efficiency. We use, in this work, the following expression for the PCFs considered [25]:…”
Section: Numerical Aperturementioning
confidence: 99%
“…[1][2][3][4][5] The flexible control of air hole allows the construction of complex dualcore or multicore structures. 6,7 Couplers, which can guide light power to other optical components in appropriate proportions, are essential for all-fiber systems and have been extensively applied in optical fiber sensing systems and coherent optical communication systems.…”
Section: Introductionmentioning
confidence: 99%